RANCANG BANGUN SISTEM ADMINISTRASI PERIZINAN KURSUS UNTUK MENINGKATKAN PELAYANAN MASYARAKAT PADA PUSAT PEMERINTAHAN - Novi Cholisoh; Henderi Henderi; Siti Khodijah (Journal Cerita: Creative Education of Research in Information Technology and Artificial Informatics, 2019)
The One Stop Integrated Services Investment Office (DPMPTSP) is one part of the Regency / City Government Center that serves licensing, one of which is the course. In practice, some regencies / cities actually have an online licensing system, besides that DPMPTSP also has its own website for course licensing but in practice both application systems are rarely used by people who want to take care of permits for various reasons, including administrative requirements that are difficult, access constraints that are sometimes problematic, the length of response time is compared to direct dating and so on. The purpose of this study is to find out the process of licensing the course, create an effective and efficient licensing system concept, and create a concept of a fast and accurate licensing system course. So the authors get alternative solutions to the problem that the public must be familiar with the online system and procedures in licensing the course should not be too long so that the community is easier to manage permits, besides the proposed system, is expected to be a companion to the existing licensing system dealing with dating directly.